Some Types of Compactness in Bitopological Spaces - Jabbar, N .A.; Nasir, A. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we give the concept of N-open set in bitopological spaces, where N is the first letter of the name of one of the authors, then we used this concept to define a new kind of compactness, namely N-compactness and we define the N-continuous function in bitopological spaces.         We study some properties of N-compact spaces, and the relationships between this kind and two other known kinds which are S-compactness and pair-wise compactness.